2019
DOI: 10.1515/hsz-2018-0421
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-6165 downregulates insulin-like growth factor-1 receptor (IGF-1R) expression and enhances apoptosis in SW480 cells

Abstract: MicroRNAs are small non-coding RNAs that are implicated in various biological processes. Hsa-miR-6165 (miR-6165), located in the p75NTR gene, is known to induce apoptosis in human cell lines, but its mechanism of action is not fully understood yet. Here, we predicted the insulin-like growth factor 1 receptor (IGF-1R) gene as a bona fide target for miR-6165. The overexpression of miR-6165 in SW480 cells resulted in significant downregulation of IGF-1R expression as detected by real time quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Abnormal expression of miRNAs is a feature of human malignancies and frequently leads to either oncogenesis or tumor suppression (21,22). Increasing evidence has demonstrated that miR-101 is downregulated in various types of cancer and inhibits the development and progression of cancer (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of miRNAs is a feature of human malignancies and frequently leads to either oncogenesis or tumor suppression (21,22). Increasing evidence has demonstrated that miR-101 is downregulated in various types of cancer and inhibits the development and progression of cancer (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that can directly regulate the levels of most mRNAs 10 . It has been found that the expression of miR‐6165 is downregulated in cancers and is related to the progression of cancers 11,12 . However, its effect on HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…COAD is the most common intestinal tumor worldwide, especially in women ( Hassanlou et al, 2019 ), and has been reported to be associated with many oncogenes ( Yin et al, 2017 ). Existing literature reports CCT6A to possess oncogenic features in a various human cancer ( Di Meo et al, 2019 ; Huang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%